TINJAUAN YURIDIS TERHADAP PERKARA PERMOHONAN PEMBATALAN PERKAWINAN DI PENGADILAN AGAMA (STUDI KASUS PUTUSAN PENGADILAN AGAMA LEBONG NOMOR: 0059/PDT.G/2015/PA.LBG.) - Sudarmadi, Sudarmadi (UIN Fatmawati Sukarno Bengkulu, 2017)
Marriage in Indonesia is regulated in Law no. 1 of 1974 concerning marriage, and Government Regulation of the Republic of Indonesia No. 9 of 1975 on the Implementation of Act No.1 of 1974. then for the people of Islam also apply Presidential Instruction No.1 Year 1991 on Compilation of Islamic Law as a complement of the Law No. 1 Year 1974. In the case of the position of this research object, that the applicant as a woman (wife) feels never divorced with her husband. However, her husband believes that she has divorced her, so the husband marries another woman. So the wife declared the marriage illegitimate, because it violates the provisions, namely when the husband is married to the second wife, the husband did not ask permission to the first wife, in addition to no permission of polygamy from the Religious Courts. So the first wife applied for a cancellation of marriage to the Religious Court in order for the second marriage to be canceled. The type of research used is qualitative research, which referred to qualitative research is a research procedure that produces descriptive data in the form of words or verbal from the people and behavior observed. Based on the formulation of the problem and research objectives, the approach method used is the juridical approach. Juridically this research may include research on legal principles, legal system, legal synchronization, legal history, and comparative law. Research location at Lebong Religious Court. The data used in this study consist of primary data and secondary data. The data obtained from both the literature and the interview will be analyzed by using qualitative analysis method, a research procedure that produces analytical descriptive data. The result of the research found that the judges of Lebong Religious Court on Marriage Cancellation with decision number 0059 / Pdt.G / 2015 / PA Lbg was rejected by the panel of judges so that the marriage of the Plaintiff’s husband with the Defendant was still legally valid and the Defendant still got his wife rights. In the contents of the decision filed a petition for the cancellation at the Lebong Religious Court, which was then registered in the case Number 0059 / Pdt.G / 2015 / PA.Lbg. which consists of three judges did not all agree with the decision. One judge argued differently from the majority of judges. Opinions differ from minority judges included in the content of the verdict called dissenting opinion.